Amenorea Sekunder: Tinjauan dan Diagnosis - Suparman, Erna; Suparman, Eddy (UNIVERSITAS SAM RATULANGI, 2017)
Abstract: Secondary amenorrhea occurs when a woman in reproductive age who has experienced menstruation, at a sudden stops menstruating for at least three consecutive months. The basic principle underlying the physiology of menstrual function is composed of multiple organ systems with their appropriate compartments in which the menstrual cycle depends on, as follows: compartment I, disorders of the uterus; compartment II, disorders of the ovary; compartment III, disorders of the anterior pituitary; and compartment IV, disorders of the central nervous system (hypothalamus). Finding the cause of secondary amenorrhoea can be done by doing some tests or trials. Determination of the location of the specific anatomical defect is useful to obtain appropriate treatment according to the cause of amenorrhea.Keywords: secondary amenorrhoeaAbstrak: Dikatakan amenorea sekunder bila seorang wanita usia reproduktif yang pernah mengalami haid, tiba-tiba haidnya berhenti untuk sedikitnya 3 bulan berturut-turut. Prinsip dasar yang mendasari fisiologi dari fungsi menstruasi memungkinkan penyusunan beberapa sistem kompartemen yang tepat di mana siklus menstruasi bergantung, yaitu: kompartemen I gangguan pada uterus, kompartemen II gangguan pada ovarium, kompartemen III gangguan pada hipofisis anterior, dan kompartemen IV gangguan pada sistem saraf pusat (hipotalamus). Gangguan ini sering berhubungan dengan keadaan stres (wanita pengungsi, dipenjara, hidup dalam ketakutan), atlit wanita, atau anoreksia nervosa dan bulimia. Mencari penyebab amenorea dapat diperoleh dengan melakukan beberapa uji atau percobaan. Penentuan lokasi defek anatomis spesifik sangat bermanfaat untuk mendapatkan penanganan yang sesuai dengan penyebab amenore.Kata kunci: amenorea sekunder